Modelling deployment pipelines for co-simulations with graph-based metadata. (3rd November 2021) - Reiterer, Stefan H.; Kalab, Michael
In complex mechatronic systems, co-simulations need to be conducted to test the behaviour of larger systems. DevOps tools and methods are used to make the development of simulation models for mechatronic systems efficient. For this purpose, a graph-based metadata model is introduced to describe the process to autogenerate code for build servers. It also makes build pipelines reusable and suitable for safety critical software components. We discuss how DevOps processes for mechatronic systems are modelled as a graph, define the data structure formally and present algorithms for automatic code generation and representation within a NoSQL graph database. In addition, we compare different optimisation strategies for build and deployment schedules.